Analisis Disposisi Matematis Siswa dalam Pembelajaran Matematika di Kelas XI SMA Negeri 3 Tambun Selatan (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to analyze the mathematical disposition of 11th-grade students at SMA Negeri 3 Tambun Selatan in learning mathematics. Mathematical disposition refers to the tendency to think and behave positively towards mathematics, encompassing seven main indicators as defined by the NCTM: self-confidence, perseverance, persistence, interest, reflection, tolerance, and appreciation of the role of mathematics. This research employed a descriptive qualitative method using an open-ended questionnaire consisting of 42 statements based on the seven indicators of mathematical disposition. Data were analyzed through the stages of data reduction, presentation, and conclusion drawing. The results indicated that appreciation of the role of mathematics in culture and values was the most dominant indicator among students, whereas persistence and perseverance in solving mathematical tasks scored the lowest. Overall, the mathematical disposition of students in the 11th grade at SMA Negeri 3 Tambun Selatan was found to be relatively low. These findings highlight the need for efforts to improve students' mathematical disposition, particularly in the areas of perseverance and persistence in completing mathematical tasks.